Antimicrobial susceptibility and characterization of metallo-β-lactamases, extended-spectrum β-lactamases, and carbapenemases of Bacillus cereus isolates. (May 2018) - Torkar, Karmen Godič; Bedenić, Branka
Abstract: The susceptibility of 66 clinical and environmental B. cereus isolates were tested to selected antimicrobials by a broth microdilution method. All strains were resistant to β-lactams and susceptible to gentamicin and imipenem. Sixty-five (98.5%) isolates were susceptible to meropenem and ciprofloxacin and 74.2% to azithromycin. Significant differences in MIC values between environmental and clinical isolates were not demonstrated ( p  > 0.05). According to the disc diffusion method, 80.3%–98.5% of the strains were resistant to one or more of four cephalosporins. The presence of genes for B. cereus β-lactamases BCI, BCII, BCIII, extended-spectrum β-lactamases from the CTX and TEM family and the carbapenemases belonging to IMP and VIM family was studied. Bla II genes were expressed in all isolates; the PCR products for bla III were also detected in two strains, but none of them was positive for bla I. The amplicon of the family bla CTX-M, mostly M-1 and M-15, was confirmed among 68.2% of the isolates, while were bla VIM -like genes determined in 21.2% of the samples. Highlights: The susceptibility of clinical and environmental B. cereus isolates was tested. Apart from metallo-β-lactamases, B. cereus can form different types of ESBLs. The ESBLs from the CTX and TEM family were confirmed in 68% of B. cereus strains. Carbapenemases belonging to VIM family were determined in 21% of the samples. B. cereus could be a precursor of transmittable MBLs to other pathogenic species.